ETUDE DE LA QUALITE PHYSICOCHIMIQUE ET DE LA CONTAMINATION METALLIQUE DES EAUX DE SURFACE DU BASSIN VERSANT DE BEHT (MAROC) - Ferdaous, Lakhili; Mohammed, Benabdelhadi; Nouzha, Bouderka; Hamid, Lahrach; Abrerrahim, Lahrach (European Scientific Journal, ESJ, 2015)
The Beht watershed is located in the north-west of Morocco. It occupies the southwest part of the Sebou basin. The study was carried out to analyze the physico-chemical parameters (T °, pH, EC, nitrates and chlorides) and assessment of contamination by trace elements (Al, As, Cd, Cr, Cu, Fe, Mn, Ni and Pb). Thus, water samples were taken at 15 sites in November 2013. The analysis showed an alkaline pH (between 8 and 8.8), the temperature fluctuates between 12 and 16°C and conductivity varies between 183 and 565 µs/cm. These results are within the recommended standards (WHO, 1984; MATEE, 2002). Laboratory analyzes have shown that the various parameters and heavy metals contents are weak which reflect the fact that in general the surface water in the Upper Beht has good quality. These results are almost the same as the Guigou river water (Akil & al. 2013), but lower than what is reported by Jeddi & al. (2013) for the downstream of Beht basin which contains a large industrial activity. In order to establish a link between physicochemical parameters and metal while assessing better the impact of human activity on the water quality of the Oued Beht, we conducted a statistical analysis by the CPA. This allowed to identify Pb, Fe, As, and Cu as pollution indicators. The origin of those elements is anthropogenic. It is believed that despite the weak contents of these elements, it is essential to set up a vigilance, to monitor their evolution and continuing the sampling and analysis.